Citizen Trust, Perceived Surveillance, and Polycentric Governance Participation in Indonesian Smart City Programs - Arya Ganendra; Jasmila Tanjung (Open Access Indonesia Journal of Social Sciences, 2026)
Smart city programs in Indonesia expand digital governance infrastructure while raising concerns about citizen surveillance and data privacy. Understanding how perceived surveillance affects citizen trust and participation in polycentric governance structures is critical for sustainable smart city development. This study examined 352 citizens across nine Indonesian cities representing three administrative tiers (Tier-1: Jakarta, Bandung, Surabaya; Tier-2: Semarang, Makassar, Medan; Tier-3: Palembang, Balikpapan, Manado) to investigate the relationships among perceived surveillance intensity, citizen trust in governance institutions, and participation in polycentric governance mechanisms. Hierarchical multiple regression analysis revealed a statistically significant model explaining 42.1% of variance in citizen trust (R² = 0.421, adjusted R² = 0.399, f² = 0.727). Facial recognition perceived intensity demonstrated the strongest negative predictor (β = -0.378, 95% CI [-0.498, -0.258]), while multi-stakeholder governance participation showed the strongest positive predictor (β = 0.334, 95% CI [0.218, 0.450]). Additional significant predictors included closed-circuit television surveillance intensity (β = -0.312), citizen feedback mechanisms (β = 0.298), data transparency (β = 0.287), decentralized decision-making participation (β = 0.256), governance literacy (β = 0.213), e-government service use (β = 0.189), and educational attainment (β = 0.145). These findings indicate that while surveillance technologies undermine institutional trust, inclusive governance processes and transparency mechanisms strengthen citizen confidence. Indonesian smart city programs should prioritize polycentric governance structures, data transparency, and digital literacy initiatives to mitigate surveillance-related trust erosion. Results support policy recommendations emphasizing stakeholder participation, technological accountability, and institutional transparency as essential components of citizen-centric smart city governance.